Silly Tilly and the Easter Bunny - Hoban, Lillian (New York, NY : Trophy, 1989)
Silly Tilly Mole is so forgetful and silly on Easter morning that she cannot find her bonnet and fails to let the Easter Bunny into the house.
003-007.
390
390
Accelerated Reader AR
Keywords: Easter -- Fiction; Moles (Animals) -- Fiction; Rabbits -- Fiction